On the biology of the Spectacled Eider - Kistchinski, A A; Flint, V E (Wildfowl, 1974)
Data on the numbers, breeding, and diet of the Spectacled Eider Somateria fischeri were obtained in 1971 in the delta of the Indigirka river. This eider breeds in the low tundra with numerous shallow lakes and flooded depressions, most abundantly in the maritime half of the delta (thirty-three to sixty pairs per 10 km) and rarely in the inland tundras. There are about 17,000 pairs in spring with a 1:1 sex ratio. Eiders nest scattered in the uniform wet tundra or several near one another on lake islets. Nesting in colonies of gulls and terns provides a protection from predators. However, large gulls themselves destroy many eider nests; therefore, only nests within the defended territories of gull pairs have a chance of surviving. Only drakes in full plumage appear at the breeding grounds. Variations in female plumage (possibly correlated with age) are described. In 1971, nearly 50% of females did not start to breed. There was a great loss of clutches from gull predation. Many ducks had repeat nests but not more than 10-15% seemed to be successful. The first clutches averaged 5.56 eggs; all clutches, including repeated, 3.74. Population increase by the end of summer was unlikely to be more than 15-25%. Non-breeding and unsuccessful females remained during the whole of July. The bulk of the food at courtship time was larvae of crane-flies Prionocera spp., and from the end of June till the beginning of August larvae of caddisflies. Many kinds of other invertebrates were consumed in July, and many seeds of Ranunculus pallasii on first arrival in June as well as at the end of July and beginning of August. Seasonal changes in eider's diet are probably correlated with the dynamics of abundance of food items.